Enhanced Bioavailability of Dihydrotanshinone I–Bovine Serum Albumin Nanoparticles for Stroke Therapy - Ren, Yanru; Feng, Yicheng; Xu, Kunyao; Yue, Saisai; Yang, Tiantian; Nie, Kaili; Xu, Man; Xu, Haijun; Xiong, Xin; Körte, Fabian; Barbeck, Mike; Zhang, Peisen; et al. (Frontiers in Pharmacology, 2021)
Dihydrotanshinone I (DHT) is a natural component in Salvia miltiorrhiza and has been widely researched for its multiple bioactivities. However, poor solubility and biocompatibility of DHT limit its desirable application for clinical purposes. Herein, DHT was encapsulated with bovine serum albumin (BSA) to enhance bioavailability. Compared to free DHT, DHT–BSA NPs (nanoparticles) showed an improved solubility in normal saline and increased protection against hydrogen peroxide–induced oxidative damage in PC12 cells. In addition, DHT–BSA NPs administered by intravenous injection displayed a significant efficacy in the middle cerebral artery occlusion/reperfusion models, without any impact on the cerebral blood flow. In summary, DHT–BSA NPs show an enhanced bioavailability compared with free DHT and a successful penetration into the central nervous system for stroke therapy, demonstrating their application potential in cardio–cerebrovascular diseases.